2007
DOI: 10.1007/s10705-006-9073-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mass balance in fields irrigated with liquid swine waste

Abstract: Over the past 15-years, swine-producing confined animal feeding operations (CAFOs) have proliferated throughout the Southeastern United States, particularly in North Carolina. Waste at these facilities is collected in open-air lagoons and the liquid phase is land-applied as fertilizer by sprinkler irrigation. Numerous investigations have focused on individual aspects of the fate of nitrogenous liquid waste, but none has attempted a comprehensive analysis of post-application transformations and losses. On three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 57 publications
7
15
0
Order By: Relevance
“…The addition of PS has been reported to improve the N status of soils for agricultural or environmental purposes (Chantigny et al, 2001;Daudén and Quílez, 2004;Whalen and DeBerardinis, 2007;Cela et al, 2011). Although the total N in the PS (1.00-1.41 g total M kg -1 ) is lower than Chantigny et al (2001) at 86 g total N kg -1 , our results are still consistent with the literature because at all stages of sampling, D1 and D2 plots have higher total N than control due to PS additions.…”
Section: Changes To Soil Properties With Ps Additionssupporting
confidence: 90%
See 1 more Smart Citation
“…The addition of PS has been reported to improve the N status of soils for agricultural or environmental purposes (Chantigny et al, 2001;Daudén and Quílez, 2004;Whalen and DeBerardinis, 2007;Cela et al, 2011). Although the total N in the PS (1.00-1.41 g total M kg -1 ) is lower than Chantigny et al (2001) at 86 g total N kg -1 , our results are still consistent with the literature because at all stages of sampling, D1 and D2 plots have higher total N than control due to PS additions.…”
Section: Changes To Soil Properties With Ps Additionssupporting
confidence: 90%
“…Contents of NO3 --N in PC2-D2 and CS2-D2 are 7X (109 mg NO3 --N kg -1 vs. 15.2 mg NH4 + -N kg -1 ) and 10X (73.6 mg NO3 --N kg -1 vs. 7.3 mg NH4 + -N kg -1 ), respectively compared to NH4 + -N in the same sampling events. The higher amounts of NO3 --N compared to NH4 + -N after two time additions of PS in the study site is consistent with nitrification of NH4 + -N in PS added to soils in Canada (Chantigny et al, 2001;Whalen and DeBerardinis, 2007).…”
Section: Changes To Soil Properties With Ps Additionssupporting
confidence: 81%
“…Nitrate-N leaching losses have been reported after application of liquid swine manure in agricultural systems. Experiments conducted in North Carolina spray fields reported that leaching losses below 20 cm after application of liquid swine manure ranged from 8 to 45 kg N ha -1 , which represented on average 13% of applied manure N (Whalen and DeBerardinis 2007). Average annual tile drain water NO 3 -N loading loss for a cornsoybean rotation amended with injected liquid swine manure ranged from 12 to 40 kg N ha -1 (6 year average 20 kg N ha -1 ), which was not significantly different than average annual tile NO 3 -N loading loss after application of similar amounts of fertilizer N (Bakhsh et al 2005).…”
Section: Soil Profile Toc Tn No 3 -N and Inorganic-n Contentmentioning
confidence: 99%
“…Spring barley recovered *50% of cattle slurry manure N within 50 days of plant emergence in spring barley cropping systems (Peterson 2006). Whalen and DeBerardinis (2007) applied liquid swine manure at low and high rates to a spray field in North Carolina planted to coastal bermudagrass in summer and seeded to tall fescue in winter. They constructed N budgets for the period spanning 14-19 days post-application.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate can be reduced to N 2 by denitrifying bacteria in anaerobic micro zones and is then lost to the atmosphere. Some research has evaluated the nitrogen mass balance in grassland irrigated with liquid swine waste at a typical nitrogen load (40-130 kg N ha −1 ) (Whalen and DeBerardinis 2007). Those authors found that plant assimilation represented the most important nitrogen sink, whereas leaching, volatilization, and accumulation in the inorganic phase assumed roughly equal importance.…”
mentioning
confidence: 99%